2012
DOI: 10.1111/j.1439-0418.2012.01733.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a direct test of baculovirus resistance in wild codling moth populations

Abstract: The occurrence of resistance of codling moth (CM, Cydia pomonella L.) to Cydia pomonella granulovirus (CpGV) used as biological control agent revealed the need for fast and reliable resistance monitoring methods. Here, we describe the development of a laboratory resistance test that is directly performed on larvae extracted from infested apples. This test is based on a 14-day bioassay at a discriminative CpGV concentration of 2 · 10 5 occlusion bodies/ml diet and can be applied to L1-L4 larvae. Information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…From 2005 on, however, the emergence of field resistance of CM populations against CpGV products was detected in Germany and France (11,12). Meanwhile, CpGVresistant CM populations have been documented in 38 orchards, mainly organic apple orchards from different European countries, including Germany (22 orchards), France (3 orchards), Switzerland (22 orchards), Italy (6 orchards), Austria (2 orchards), The Netherlands (2 orchards), and the Czech Republic (1 orchard) (13)(14)(15)(16)(17). Some of these field populations were 1,000 to 100,000 times less susceptible to CpGV-M than were typical susceptible larvae (13).…”
mentioning
confidence: 99%
“…From 2005 on, however, the emergence of field resistance of CM populations against CpGV products was detected in Germany and France (11,12). Meanwhile, CpGVresistant CM populations have been documented in 38 orchards, mainly organic apple orchards from different European countries, including Germany (22 orchards), France (3 orchards), Switzerland (22 orchards), Italy (6 orchards), Austria (2 orchards), The Netherlands (2 orchards), and the Czech Republic (1 orchard) (13)(14)(15)(16)(17). Some of these field populations were 1,000 to 100,000 times less susceptible to CpGV-M than were typical susceptible larvae (13).…”
mentioning
confidence: 99%
“…Therefore, dosages of 10 4 –10 6 OB/ml used in the bioassays can be applied to discriminate between susceptible and resistant neonate individuals in a population. For older instars showing some developmental tolerance to CpGV‐M, a discriminative concentration of 2 × 10 4 OB/ml was proposed for resistance testing (Schulze‐Bopp and Jehle ).…”
Section: Discussionmentioning
confidence: 99%
“…Either this value alone or in combination with the LC 50 value can be successfully used for identification of resistance in a population. The development of a fast resistance test that is based on the CpGV induced mortality of larvae extracted from apples will even accelerate the identification process of resistance (Schulze‐Bopp and Jehle ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2005, resistance against the widely used isolate CpGV-M has been reported from different countries in Europe [41,43,44]. In a multination monitoring program, Schulze-Bopp and Jehle [45] identified that 70% of CM were resistant or partly resistant to CpGV across multiple orchards in Germany, Austria, Switzerland, Italy, and the Netherlands. The recent research by Sauer et al [46] described autosomal and dominant inheritance of this resistance and demonstrated cross-resistance to different CpGV genome groups.…”
Section: Insecticides Resistancementioning
confidence: 99%